A granulated ferrous chloride tetrahydrate and a method for its production
Patent Information
- Application Number
- CN202611051007.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
如公开号为CN111170373A的中国专利公开了一种四水氯化亚铁的制备方法,其通过盐酸酸洗废液溶解钢铁氧化皮、还原铁粉置换、过滤、蒸发浓缩、降温结晶和离心分离获得四水氯化亚铁,并指出传统工艺存在产品纯度低、结晶颗粒小和分离回收率低等问题,但该方案主要围绕母液资源化与结晶控制展开,未针对二级颗粒的重结晶桥接、致密表层和开放孔隙之间的平衡建立完整设计
1.本发明通过将四水氯化亚铁原级晶体经重结晶桥接构筑为二级颗粒,使细小晶体由分散状态转变为可计量颗粒状态,降低粉体扬尘、架桥和流动波动风险,同时保持四水氯化亚铁本身的化学组成,适合连续投料和批量储运。
Smart Images

Figure CN122897443A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic salt material preparation, specifically to a granulated ferrous chloride tetrahydrate and its preparation method. Background Technology
[0002] Ferrous chloride tetrahydrate, as an important ferrous salt raw material, can be used in water treatment, inorganic synthesis, formulation of reducing systems, metal ion regulation, and preparation of iron-containing functional materials. In industrial storage, transportation, and continuous feeding processes, this type of inorganic salt material not only needs to maintain a stable ferrous state but also requires good particle flowability, measurability, and solubility. While powders or fine crystals have a larger contact area for dissolution, they are prone to dust generation, moisture absorption, bridging, and metering fluctuations during packaging, transportation, and feeding. Granular products are more suitable for automated feeding and batch storage, but there are interrelationships between their internal bonding strength, surface density, pore channels, and the state of crystal water. Therefore, establishing a granular form of ferrous chloride tetrahydrate with controllable particle size, low oxidation risk, stable structure, and solubility is of practical significance for improving the storage and transportation safety, feeding efficiency, and industrial application stability of ferrous salt products.
[0003] Current methods for preparing ferrous chloride tetrahydrate typically emphasize solution purification, concentration, cooling crystallization, and solid-liquid separation. However, they pay insufficient attention to the particle morphology after crystallization, oxidation control during wet granulation, and the regulation of the outer layer structure of the particles. For example, Chinese patent CN111170373A discloses a method for preparing ferrous chloride tetrahydrate, which involves dissolving steel oxide scale in hydrochloric acid pickling waste liquid, reducing iron powder for replacement, filtration, evaporation and concentration, cooling crystallization, and centrifugation to obtain ferrous chloride tetrahydrate. It points out that traditional processes suffer from low product purity, small crystal particles, and low separation and recovery rates. However, this method mainly focuses on mother liquor resource utilization and crystallization control, without establishing a complete design for the recrystallization bridging of secondary particles, the balance between dense surface layers and open pores. Other technical documents have studied the influence of hydrochloric acid and ferrous chloride concentrations on the rate of ferrous chloride oxidation by oxygen, indicating that oxygen contact and acidity control in the ferrous salt system affect oxidation risk. However, these studies do not address the synergistic control issue between improving fluidity and maintaining stability under low oxygen conditions during wet granulation. Summary of the Invention
[0004] The purpose of this invention is to provide a granulated ferrous chloride tetrahydrate and its preparation method, which solves the current problems of difficulty in balancing the processing fluidity and oxidation stability of ferrous chloride tetrahydrate, as well as the difficulty in balancing structural integrity and solubility.
[0005] This invention constructs secondary particles by recrystallizing primary crystals and then recrystallizing them using a saturated ferrous chloride hydrochloric acid solution to form a dense surface layer. Under low-oxygen conditions, it controls the particle bonding strength, surface barrier, and internal porosity, thereby mitigating the risk of water-oxygen contact during granulation through acidity and surface control. The adverse effects of the dense structure on the dissolution channels are mitigated by the regulation of open pores, thus balancing fluidity, stability, structural integrity, and solubility.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A granulated ferrous chloride tetrahydrate is disclosed, wherein the granulated ferrous chloride tetrahydrate is a secondary particle with an intergranular recrystallization connection structure formed by multiple primary ferrous chloride tetrahydrate crystals, and the secondary particle has a dense surface layer on its outer layer; wherein the particle size D50 of the secondary particle is 0.8-2.5 mm, the particle size D50 of the primary ferrous chloride tetrahydrate crystal is 50-150 μm, the free hydrochloric acid content (HCl) is 0.02-0.30 wt%, the total iron content (Fe) is 27.3-28.1 wt%, the water of crystallization content is 35.5-36.2 wt%, the bulk density is 1.2-1.8 g / cm³, the trivalent iron content is ≤0.05 wt%, the thickness of the dense surface layer is 20-80 μm, and the particle open porosity of the secondary particle is 8-20%. Unless otherwise specified, the ferrous chloride content in this invention is calculated as anhydrous ferrous chloride, the free hydrochloric acid content is calculated as HCl, and the total iron content is calculated as Fe.
[0007] Furthermore, the primary ferrous chloride tetrahydrate crystals are prepared through the following steps: A1. Add ferrous chloride tetrahydrate to tap water and dissolve it at 40-65℃; A2. Add hydrochloric acid to the solution obtained in A1 to make the ferrous chloride content in the solution 18-22 wt% and the free hydrochloric acid content 0.05-0.30 wt%, and keep it warm under a nitrogen atmosphere for 10-60 min; A3. Cool the solution obtained in A2 to 15-25℃ and keep it at that temperature for 0.5-2.0h, then separate the solid and liquid phases to obtain primary ferrous chloride tetrahydrate crystals with a particle size D50 of 50-150μm.
[0008] Furthermore, the dense surface layer is formed through the following steps: B1. Ferrous chloride tetrahydrate is added to the mother liquor containing hydrochloric acid obtained from the solid-liquid separation in A3, and a saturated ferrous chloride-hydrochloric acid solution is prepared at 20-30℃, wherein the free hydrochloric acid content is 0.20-0.80 wt%. B2. Filter to remove undissolved solids to obtain the surface-forming liquid; B3. The surface layer forming liquid obtained in B2 is sprayed onto the surface of wet particles formed by low-shear granulation and ripening of the primary crystals of ferrous chloride tetrahydrate. The amount sprayed each time is 0.5-5.0 wt% of the mass of the wet particles. After each spraying, the particles are ripened for 10-30 minutes. This process is repeated 1-3 times to form the dense surface layer.
[0009] Furthermore, the secondary particles are formed through the following steps: C1. The primary ferrous chloride tetrahydrate crystals are mixed with the surface-forming liquid, wherein the amount of liquid added is 2-10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals; C2. The mixture obtained in C1 is granulated in a low-shear granulation device at 18-30℃ and 20-60rpm for 5-20min to obtain wet granules; C3. The wet particles obtained from C2 are aged for 0.5-2.0 hours to form recrystallization bridges between adjacent primary crystals.
[0010] Furthermore, the wet particles obtained from C3 are dried at 20-35°C under a nitrogen atmosphere for 2-8 hours. The drying is stopped when the water of crystallization content reaches 35.5-36.2 wt%, thus obtaining the granulated ferrous chloride tetrahydrate.
[0011] Furthermore, the angle of repose of the granulated ferrous chloride tetrahydrate is 25-40°.
[0012] As a concept of this invention, the present invention employs a design that uses primary crystal recrystallization to bridge and form secondary particles, and then uses a saturated ferrous chloride hydrochloric acid solution to recrystallize and construct a dense surface layer. This design is primarily used to achieve a synergistic balance between processing fluidity and oxidation stability. Existing ferrous chloride tetrahydrate, if simply refined to increase the dissolution contact area, increases interparticle friction and hygroscopic contact, easily leading to difficulties in metering and conveying and the risk of ferrous oxidation. If simply densification is used to improve storage stability, it may hinder the penetration of the aqueous phase and reduce dissolution availability. This invention, through matching the primary crystal particle size, secondary particle size, free hydrochloric acid content, water of crystallization content, bulk density, open porosity, and dense surface layer thickness, enables the intercrystalline bonds to provide granulation strength, reduces air and moisture intrusion into the surface layer, and retains dissolution channels in the internal pores, thereby balancing structural integrity, fluidity, oxidation stability, and dissolution availability.
[0013] This invention also discloses a method for preparing granulated ferrous chloride tetrahydrate, comprising the following steps: S1. Add ferrous chloride tetrahydrate to tap water and dissolve it at 40-65℃. Add hydrochloric acid to make the ferrous chloride content in the resulting solution 18-22wt% and the free hydrochloric acid content 0.05-0.30wt%. After keeping the solution at a nitrogen atmosphere for 10-60min, cool the resulting solution to 15-25℃ and keep it at that temperature for 0.5-2.0h. Separate the solid and liquid to obtain primary ferrous chloride tetrahydrate crystals with a particle size D50 of 50-150μm. S2. Add ferrous chloride tetrahydrate to the mother liquor containing hydrochloric acid obtained from the solid-liquid separation in step S1, and prepare a saturated ferrous chloride-hydrochloric acid solution at 20-30℃, wherein the free hydrochloric acid content is 0.20-0.80wt%; filter to remove undissolved solids to obtain the surface-forming liquid; S3. Mix the primary ferrous chloride tetrahydrate crystals with the surface forming liquid, wherein the amount of liquid added is 2-10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals; granulate the resulting mixture in a low-shear granulation device at 18-30℃ and 20-60 rpm for 5-20 min, and then mature it for 0.5-2.0 h to obtain wet granules; S4. Spray the surface forming liquid onto the surface of the wet particles 1-3 times, and allow it to mature for 10-30 minutes after each spraying to form a dense surface layer on the outer layer of the wet particles. S5. The particles obtained in S4 are dried at 20-35℃ under a nitrogen atmosphere for 2-8 hours to obtain granulated ferrous chloride tetrahydrate.
[0014] Furthermore, in step S1, the dissolved oxygen in the solution obtained after adding hydrochloric acid is ≤0.5mg / L, and the cooling rate is 5-20℃ / h.
[0015] Furthermore, the wet particle size D50 obtained in step S3 is 0.3-1.2 mm; in step S4, the amount sprayed each time is 0.5-5.0 wt% of the mass of the wet particles; the drying endpoint in step S5 is when the crystal water content reaches 35.5-36.2 wt%.
[0016] Furthermore, the mother liquor generated in the preparation method is recycled 1-5 times after being replenished with ferrous chloride tetrahydrate, hydrochloric acid and tap water. The ferrous chloride content in the recycled mother liquor is maintained at 18-22 wt%, and the free hydrochloric acid content is maintained at 0.05-0.80 wt%. The recycled mother liquor used before step S1 is replenished and adjusted so that the free hydrochloric acid content in the solution entering step S1 is maintained at 0.05-0.30 wt%.
[0017] Furthermore, the tap water used for dissolving ferrous chloride tetrahydrate is treated with nitrogen bubbling deoxygenation before entering the dissolution step. The treated tap water is used as the feed release index with dissolved oxygen ≤0.5mg / L, and is used to dissolve ferrous chloride tetrahydrate at 40-65℃. The resulting ferrous chloride tetrahydrate solution is then used in the hydrochloric acid addition and nitrogen atmosphere heat preservation steps.
[0018] Furthermore, the solid-liquid separation of the primary ferrous chloride tetrahydrate crystals is carried out at 15-25℃, and the solid-liquid separation method is selected from filtration and centrifugation. After solid-liquid separation, primary ferrous chloride tetrahydrate crystals with a particle size D50 of 50-150μm and a mother liquor containing hydrochloric acid are obtained, respectively. The mother liquor containing hydrochloric acid is used as the liquid source for preparing saturated ferrous chloride-hydrochloric acid solution.
[0019] Furthermore, a saturated ferrous chloride-hydrochloric acid solution is prepared at 20-30°C. Ferrous chloride tetrahydrate is added to the mother liquor containing hydrochloric acid while maintaining the presence of undissolved solids in the system. The free hydrochloric acid content is adjusted to 0.20-0.80 wt%. Subsequently, the undissolved solids are removed by filtration, and the resulting filtrate is used as the surface forming liquid in the wet particle surface spraying step.
[0020] Furthermore, the mixing of primary ferrous chloride tetrahydrate crystals with the surface-forming liquid, low-shear granulation, and maturation are all carried out under a nitrogen atmosphere. The amount of liquid added is 2-10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals, the granulation temperature is 18-30℃, the granulation speed is 20-60 rpm, the granulation time is 5-20 min, and the maturation time is 0.5-2.0 h. The resulting wet granules are then applied to the surface spraying step.
[0021] Furthermore, in the surface layer forming liquid spraying step, the total mass of wet particles before the first spraying is used as the calculation basis for the amount of each spraying. The amount of each spraying is 0.5-5.0 wt% of the mass of wet particles, and the number of sprayings is 1-3 times. After each spraying, the particles are matured within 10-30 minutes. The matured particles are then dried in a nitrogen atmosphere at 20-35℃.
[0022] Furthermore, the drying endpoint is determined by sampling and measuring the crystal water content of the particles. The test samples are taken from the particles during the drying process in a nitrogen atmosphere at 20-35℃. The test data include sample mass, crystal water content and sampling time. Particles with a crystal water content of 35.5-36.2wt% are used as the granulated ferrous chloride tetrahydrate finished product.
[0023] Furthermore, the particle size D50 of the secondary particles and the wet particle size D50 are determined based on the particle size distribution data of the particle samples, and the particle size D50 of the primary crystals is determined based on the particle size distribution data of the primary ferrous chloride tetrahydrate crystal samples. The detection data includes the sample source stage, sample state, particle size distribution curve, and D50 calculation results. The obtained D50 calculation results are used to determine the particle size range of the secondary particles, wet particles, and primary ferrous chloride tetrahydrate crystals, respectively.
[0024] Furthermore, the thickness of the dense surface layer was determined by cross-sectional observation of the dried particles. The cross-sectional sample was taken from the granulated ferrous chloride tetrahydrate finished product. The test data included cross-sectional images, surface boundary positions, surface thickness measurements of individual particles, and statistical values of the thickness of multiple particles. The obtained statistical values were used to determine whether the thickness of the dense surface layer was 20-80 μm.
[0025] Furthermore, the free hydrochloric acid content, total iron content, ferric iron content, and water of crystallization content of the granulated ferrous chloride tetrahydrate product were determined using the same batch of dried finished product as test samples. The test data included sample batch, sampling mass, test method, calculation caliber, and test results. The obtained test results were used to determine the free hydrochloric acid content as 0.02-0.30 wt%, the total iron content as 27.3-28.1 wt%, the ferric iron content as ≤0.05 wt%, and the water of crystallization content as 35.5-36.2 wt%.
[0026] As another aspect of this invention, it employs a preparation process that integrates dissolution deoxygenation, hydrochloric acid regulation, low-temperature crystallization, mother liquor preparation, low-shear granulation, surface spraying for ripening, and nitrogen-air-temperature drying. This process is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Existing processes, if focused solely on increasing particle size, easily overlook the water-oxygen contact and surface structure uniformity during wet granulation. Conversely, simply intensifying drying or densification treatment may disrupt the water of crystallization state of ferrous chloride tetrahydrate and reduce its solubility. This invention, by controlling dissolved oxygen, acidity, cooling rate, low-shear granulation intensity, wet particle ripening time, surface-forming liquid spraying amount, and drying endpoint, enables the formation of recrystallization bridges that maintain the structure between primary crystals. This allows the outer recrystallized surface layer to form under mild conditions, and the particles to complete granulation and drying in a low-oxygen environment. This simultaneously mitigates the adverse effects of oxidation, pulverization, excessive densification, and water of crystallization imbalance along the process pathway.
[0027] Recrystallization bridging primarily addresses the structural integrity and processing flowability issues of primary ferrous chloride tetrahydrate crystals after granulation. However, if the intercrystalline bonds are too strong or the particles are excessively dense, the pathway for the aqueous phase to enter the particle interior will be restricted, easily reducing solubility. The dense surface layer formed by recrystallization of saturated ferrous chloride-hydrochloric acid solution mainly reduces the contact between air and moisture and the ferrous salt and is beneficial for oxidation stability. However, if the surface layer is too thick or the acidity is too high, it may increase particle dissolution stagnation or cause excessive free hydrochloric acid. This invention, through matching the primary crystal particle size, liquid addition amount, spraying amount, maturation time, dense surface layer thickness, and open porosity, enables recrystallization bridging to provide granulation strength, the dense surface layer to provide an outer barrier, internal pores to retain dissolution channels, and the low-oxygen process to reduce the risk of wet oxidation, ultimately balancing processing flowability, oxidation stability, structural integrity, and solubility.
[0028] Beneficial technical effects 1. This invention constructs secondary particles by recrystallizing and bridging primary ferrous chloride tetrahydrate crystals, thereby transforming fine crystals from a dispersed state into a measurable particle state. This reduces the risks of powder dust, bridging, and flow fluctuations, while maintaining the chemical composition of ferrous chloride tetrahydrate itself, making it suitable for continuous feeding and batch storage and transportation.
[0029] 2. This invention forms a dense surface layer on the surface of wet particles by recrystallizing a saturated ferrous chloride-hydrochloric acid solution, which creates a certain barrier to air and moisture contact on the outer layer of the particles. The ferrous salt environment is maintained by regulating the content of free hydrochloric acid, thereby reducing the risk of increased ferric iron content during wet granulation and improving storage stability.
[0030] 3. This invention combines low-shear granulation, wet particle maturation, and surface-forming liquid spraying, which allows for the joint regulation of intercrystalline connections, outer layer densification, and internal open pores. This avoids limiting dissolution channels by simply increasing particle strength, and also avoids pulverization and insufficient flowability caused by simply retaining a loose structure. It is suitable for balancing structural integrity and solubility.
[0031] 4. This invention introduces low-oxygen control and crystal water endpoint determination in the dissolution, mixing, granulation, ripening and drying stages, so that the process is constrained around the stability of divalent iron and the tetrahydrate state, reducing the impact of excessive drying, oxidation and fluctuations in hydration state on product quality, and improving the repeatability of different batches of granular products.
[0032] 5. The present invention utilizes the mother liquor containing hydrochloric acid obtained from solid-liquid separation to prepare the surface forming liquid, and can be recycled by adding ferrous chloride tetrahydrate, hydrochloric acid and tap water, so that the ferrous chloride and acidity in the mother liquor can be further utilized, reducing material loss and facilitating the formation of a recrystallized surface layer that is compatible with the chemical composition of the particle body. Attached Figure Description
[0033] Figure 1 The figure shows the effect of the primary crystal size D50 of granulated ferrous chloride tetrahydrate on the angle of repose and the increase of ferric iron at 7d.
[0034] Figure 2 The figure shows the effect of the amount of granulated ferrous chloride tetrahydrate liquid added in this scheme on the angle of repose and the increase of ferric iron at 7d.
[0035] Figure 3 The graph shows the effect of the free hydrochloric acid content in the granulated ferrous chloride tetrahydrate surface layer formation solution on the angle of repose and the increase of ferric iron at 7 days.
[0036] Figure 4 This diagram illustrates the effect of the amount of granulated ferrous chloride tetrahydrate applied per spray on the angle of repose and the increase in ferric iron over 7 days.
[0037] Figure 5 The figure shows the effect of drying temperature on the angle of repose and the increase in ferric chloride granulation over 7 days in this scheme.
[0038] Figure 6 This is a differential particle size distribution diagram of the secondary particles in Example 1, Comparative Example 1, and Comparative Example 9 of this scheme.
[0039] Figure 7 This is a cumulative particle size distribution diagram of the secondary particles in Example 1, Comparative Example 1, and Comparative Example 9 of this scheme.
[0040] Figure 8 The diagram shows the pairing of secondary particles D50 before and after wear in Embodiment 1, Comparative Example 1, and Comparative Example 9 of this scheme.
[0041] Figure 9 This is a statistical diagram of the intercrystalline connectivity density of Example 1 and Comparative Example 9 of this scheme.
[0042] Figure 10 This is a statistical chart of the cross-sectional crack ratio for Example 1 and Comparative Example 9 of this scheme.
[0043] Figure 11 The diagram shows the thickness distribution of the dense surface layer in Embodiment 1, Comparative Example 10, and Comparative Example 11 of this scheme.
[0044] Figure 12 This is a combined graph showing the increase in ferric iron and the dissolution completion time of Example 1 of this scheme and the comparative sample.
[0045] Figure 13 This is a combined graph showing the crystal water content and ferric iron content of Example 1 of this scheme and the comparative sample.
[0046] Figure 14 The thermogravimetric (TG) curves are for Example 1, Comparative Example 6, and Comparative Example 7 of this scheme.
[0047] Figure 15The thermogravimetric (DTG) curves for Example 1, Comparative Example 6, and Comparative Example 7 of this scheme are shown.
[0048] Figure 16 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 9; where a is a low-magnification SEM image of the final product of Example 1; b is a low-magnification SEM image of the final product of Comparative Example 9; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 9; e is a high-magnification SEM or cross-sectional SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 9.
[0049] Figure 17 The images show a comparison of the TEM structures of the final product of Example 1 and the final product of Comparative Example 9; where a is a bright-field TEM image of the final product of Example 1; b is a bright-field TEM image of the final product of Comparative Example 9; c is an HRTEM image of the final product of Example 1; d is an HRTEM image of the final product of Comparative Example 9; e is a SAED result image of the final product of Example 1; and f is a SAED result image of the final product of Comparative Example 9. Detailed Implementation
[0050] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0051] Example 1 S1: Primary Crystal Preparation Take 5.000 kg of commercially available ferrous chloride tetrahydrate, with a purity ≥98.0% and an appearance of light green crystals. Take tap water treated with nitrogen bubbling for 30 min, with a dissolved oxygen content of 0.5 mg / L, and add it according to the target ferrous chloride content of 18 wt% (calculated as anhydrous ferrous chloride) in the resulting solution. Add the deoxygenated tap water to a jacketed enamel-lined reactor, heat to 40°C under a nitrogen atmosphere, start mechanical stirring at 120 rpm, add ferrous chloride tetrahydrate in batches and stir until the solid is completely dissolved. Add analytical grade hydrochloric acid to the resulting solution to adjust the ferrous chloride content to 18 wt% and the free hydrochloric acid content to 0.05 wt%, maintain the nitrogen atmosphere, and keep at 40°C for 10 min.
[0052] S2: Cooling crystallization and solid-liquid separation The solution obtained from S1 was cooled to 15°C at a cooling rate of 5°C / h and held at 15°C for 0.5h, with stirring maintained at 120 rpm during the holding period. After the holding period, the solution was filtered at 15°C, and the filter cake was washed with a mother liquor containing hydrochloric acid at 15°C to obtain primary ferrous chloride tetrahydrate crystals and a mother liquor containing hydrochloric acid. Particle size distribution testing showed that the particle size D50 of the primary ferrous chloride tetrahydrate crystals was 50 μm.
[0053] S3: Preparation of surface forming liquid Take the mother liquor containing hydrochloric acid obtained from the S2 solid-liquid separation, add commercially available ferrous chloride tetrahydrate at 20℃, and maintain a small amount of undissolved solid in the system to adjust the free hydrochloric acid content in the liquid phase to 0.20 wt%. After standing for 5 min, filter with a filter membrane to remove the undissolved solid, and obtain a clear surface-forming liquid.
[0054] S4: Low-shear granulation and maturation Weigh 1.000 kg of primary ferrous chloride tetrahydrate crystals obtained from S2, and add 20.0 g of surface-forming liquid, the amount of which is 2 wt% of the mass of the primary ferrous chloride tetrahydrate crystals. Place the mixture in a low-shear granulator and granulate for 5 min at 18°C and 20 rpm under a nitrogen atmosphere to obtain wet granules. Let the wet granules stand and mature for 0.5 h at 18°C under a nitrogen atmosphere to allow recrystallization bridging to form between adjacent primary crystals. The particle size D50 of the wet granules is 0.3 mm.
[0055] S5: Surface spraying and drying Based on a total wet granule mass of 1.020 kg before the first spray, 5.1 g of surface-forming liquid was uniformly sprayed onto the surface of the wet granules. Each spraying amount was 0.5 wt% of the wet granule mass, and the spraying was repeated once. After spraying, the granules were cured at 18℃ under a nitrogen atmosphere for 10 min. Subsequently, the granules were transferred to a nitrogen atmosphere drying oven and dried at 20℃ for 2 h. Drying was stopped when the crystal water content reached 35.5 wt%, yielding granulated ferrous chloride tetrahydrate.
[0056] S6: Quality Inspection Methods and Results The dried finished product was tested. The secondary particles had a particle size D50 of 0.8 mm, a free hydrochloric acid content of 0.02 wt%, a total iron content of 27.3 wt%, a water of crystallization content of 35.5 wt%, a bulk density of 1.2 g / cm³, an angle of repose of 33.5°, a ferric iron content of 0.05 wt%, a dense surface layer thickness of 20 μm, and a particle open porosity of 20%. Particle size was determined by measuring particle size distribution and reading D50. The dense surface layer thickness was obtained by statistically analyzing at least 30 particles from cross-sectional images. The bulk density was determined by constant volume weighing.
[0057] Features and application scenarios of this embodiment This embodiment adopts a relatively conservative low-ratio scheme and mild process conditions, with finer primary crystals, lower liquid addition, lower granulation intensity, and fewer spraying times. It is suitable for granulated ferrous chloride tetrahydrate preparation scenarios that require low-temperature processing, low liquid dosage, and fast dissolution response.
[0058] Example 2 Raw materials and proportions This embodiment uses 6.500 kg of commercially available ferrous chloride tetrahydrate and tap water deoxygenated by nitrogen bubbling as starting materials. The purity of ferrous chloride tetrahydrate is ≥98.0%, the dissolved oxygen of the tap water after bubbling with nitrogen for 45 min is 0.2 mg / L, the hydrochloric acid used is analytical grade hydrochloric acid, the nitrogen purity is ≥99.9%, and the amount of tap water added is measured according to the target caliber of 22 wt% ferrous chloride content in the resulting solution, calculated as anhydrous ferrous chloride.
[0059] Primary crystal formation process Deoxygenated tap water was heated to 65°C, and ferrous chloride tetrahydrate was added in batches under a nitrogen atmosphere with stirring at 180 rpm. After the solid was completely dissolved, hydrochloric acid was added to make the ferrous chloride content in the solution 22 wt% and the free hydrochloric acid content 0.30 wt%. The solution was then kept at 65°C under a nitrogen atmosphere for 60 min. Subsequently, the solution was cooled to 25°C at a cooling rate of 20°C / h, kept at 25°C for 2.0 h, and then centrifuged at 25°C to obtain primary ferrous chloride tetrahydrate crystals and a mother liquor containing hydrochloric acid. The particle size D50 of the primary ferrous chloride tetrahydrate crystals was 150 μm.
[0060] Surface Forming Liquid Preparation Process Ferrous chloride tetrahydrate was added to the mother liquor containing hydrochloric acid, and a saturated ferrous chloride-hydrochloric acid solution was prepared by stirring at 30°C, ensuring that visible undissolved solids remained in the system. The free hydrochloric acid content was adjusted to 0.80 wt%. After filtering to remove the undissolved solids, the surface-forming liquid was obtained.
[0061] Granulation, surface recrystallization and drying Take 1.000 kg of primary ferrous chloride tetrahydrate crystals and add 100.0 g of surface-forming liquid, the amount of liquid added being 10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals. Granulate the resulting mixture in a low-shear granulator at 30℃, 60 rpm, and a nitrogen atmosphere for 20 min to obtain wet granules with a particle size D50 of 1.2 mm. Mature the wet granules at 30℃ under a nitrogen atmosphere for 2.0 h. Using the total mass of wet granules before the first spraying (1.100 kg) as a baseline, apply 55.0 g of surface-forming liquid each time, the amount of which is 5.0 wt% of the wet granule mass, for three consecutive sprays. After each spraying, mature the granules at 30℃ for 30 min. Dry the matured granules at 35℃ under a nitrogen atmosphere for 8 h. Stop drying when the crystal water content reaches 36.2 wt%.
[0062] Quality inspection or performance testing The resulting granulated ferrous chloride tetrahydrate secondary particles had a particle size (D50) of 2.5 mm, a free hydrochloric acid content of 0.30 wt%, a total iron content of 28.1 wt%, a water of crystallization content of 36.2 wt%, a bulk density of 1.8 g / cm³, an angle of repose of 25°, a ferric iron content of 0.03 wt%, a dense surface layer thickness of 80 μm, and an open porosity of 8%. During testing, the same batch of finished products was used to statistically analyze particle size, bulk density, angle of repose, chemical composition, and cross-sectional thickness.
[0063] Features of the solution in this embodiment This embodiment adopts an optimized scheme with a higher load, resulting in larger primary crystal particle size, higher liquid addition, longer granulation time, more surface liquid spraying amount and spraying times, and larger finished particle size and higher bulk density. It is suitable for application scenarios with high requirements for stable storage and transportation, low dust and automatic feeding flowability.
[0064] Example 3 Key parameters and sample condition This embodiment prepares granulated ferrous chloride tetrahydrate samples, with a target batch size of 1,000 kg of primary crystal granulation. Tap water was treated with nitrogen bubbling for 40 min to achieve a dissolved oxygen level of 0.3 mg / L. Ferrous chloride tetrahydrate was a commercially available industrial raw material, and hydrochloric acid was analytical grade. Solid-liquid separation was performed by centrifugation. The mother liquor was recycled three times, after which ferrous chloride tetrahydrate, hydrochloric acid, and tap water were added. The ferrous chloride content in the circulating mother liquor used to prepare the surface layer formation solution was maintained at 20 wt%, and the free hydrochloric acid content was maintained at 0.50 wt%.
[0065] Preparation process 5.800 kg of ferrous chloride tetrahydrate was added to deoxygenated tap water at the target concentration and dissolved at 52 °C under a nitrogen atmosphere with a stirring speed of 150 rpm. After adding hydrochloric acid, the resulting solution contained 20 wt% ferrous chloride and 0.18 wt% free hydrochloric acid. The solution was kept at 52 °C for 30 min. Subsequently, the solution was cooled to 20 °C at a cooling rate of 10 °C / h and kept at that temperature for 1.0 h. The solution was then centrifuged at 20 °C to obtain primary ferrous chloride tetrahydrate crystals and a mother liquor containing hydrochloric acid. The particle size (D50) of the primary ferrous chloride tetrahydrate crystals was 100 μm.
[0066] Structural construction process Ferrous chloride tetrahydrate was added to a mother liquor containing hydrochloric acid to prepare a saturated ferrous chloride-hydrochloric acid solution at 25°C, ensuring a free hydrochloric acid content of 0.50 wt%. After filtration to remove undissolved solids, a surface-forming solution was obtained. 1.000 kg of primary ferrous chloride tetrahydrate crystals was weighed and 60.0 g of the surface-forming solution was added, with the liquid addition amount being 6 wt% of the primary ferrous chloride tetrahydrate crystal mass. The mixture was granulated under low shear at 24°C and 40 rpm for 12 min in a nitrogen atmosphere to obtain wet particles with a particle size D50 of 0.75 mm. The wet particles were then matured at 24°C in a nitrogen atmosphere for 1.2 h.
[0067] Post-processing Based on a total wet granule mass of 1.060 kg before the first spray, 26.5 g of surface-forming liquid was applied each time, with each application amount being 2.5 wt% of the wet granule mass. The spraying was performed twice, followed by maturation at 24℃ for 20 min after each application. The matured granules were then dried at 28℃ under a nitrogen atmosphere for 5 h. Drying was stopped when the crystal water content reached 36.0 wt%.
[0068] Quality testing methods and results The resulting granulated ferrous chloride tetrahydrate secondary particles had a particle size (D50) of 1.5 mm, a free hydrochloric acid content of 0.15 wt%, a total iron content of 27.7 wt%, a water of crystallization content of 36.0 wt%, a bulk density of 1.5 g / cm³, an angle of repose of 32°, a ferric iron content of 0.02 wt%, a dense surface layer thickness of 50 μm, and an open porosity of 14%. Particle size distribution, cross-sectional thickness, and chemical composition were all measured using samples from the same drying batch.
[0069] The process features and application directions of this embodiment This embodiment uses intermediate parameter combinations and circulating mother liquor conditions to demonstrate the process adaptability of mother liquor recycling, medium particle size, medium surface thickness, and controlled drying endpoint. It is suitable for scenarios in conventional industrial batch production that take into account flowability, stability, and material utilization.
[0070] Example 4 I. Preparation Object and Raw Material State Using 5.500 kg of commercially available ferrous chloride tetrahydrate as raw material, with a purity ≥98.0%, and tap water treated with nitrogen bubbling for 35 min as solvent, the dissolved oxygen content after treatment was 0.4 mg / L. Hydrochloric acid was of analytical grade, and nitrogen purity was ≥99.9%. In this embodiment, the mother liquor was recycled 5 times. The ferrous chloride content in the recycled mother liquor used to prepare the surface layer forming solution was maintained at 21 wt%, and the free hydrochloric acid content was maintained at 0.35 wt%. The amount of tap water added was measured according to the target caliber of 21 wt% ferrous chloride content (calculated as anhydrous ferrous chloride) in the resulting solution.
[0071] II. Preparation of Primary Crystals Deoxygenated tap water was added to the reactor and heated to 58°C. Ferrous chloride tetrahydrate was added under a nitrogen atmosphere, and the stirring speed was 160 rpm. After the ferrous chloride tetrahydrate dissolved, hydrochloric acid was added. The resulting solution contained 21 wt% ferrous chloride and 0.12 wt% free hydrochloric acid. The solution was kept at 58°C for 45 min. The solution was then cooled to 18°C at a cooling rate of 15°C / h and kept at that temperature for 1.6 h. The solution was then filtered at 18°C to obtain primary ferrous chloride tetrahydrate crystals and a mother liquor containing hydrochloric acid. The particle size D50 of the primary ferrous chloride tetrahydrate crystals was 75 μm.
[0072] III. Saturated Solution Preparation and Granulation Ferrous chloride tetrahydrate was added to a mother liquor containing hydrochloric acid at 23°C to introduce undissolved solids into the system. The free hydrochloric acid content was adjusted to 0.35 wt%. After filtration to remove the undissolved solids, a surface-forming liquid was obtained. 1.000 kg of primary ferrous chloride tetrahydrate crystals were taken and 80.0 g of the surface-forming liquid was added, with the liquid addition amount being 8 wt% of the mass of the primary ferrous chloride tetrahydrate crystals. The mixture was placed in a low-shear granulator and granulated for 18 min under a nitrogen atmosphere at 22°C and 50 rpm to obtain wet granules with a particle size D50 of 0.95 mm. The wet granules were then matured at 22°C for 1.5 h.
[0073] IV. Surface Treatment and Drying Based on a total wet granule mass of 1.080 kg before the first spray, 16.2 g of surface-forming liquid was applied each time, with each application amount being 1.5 wt% of the wet granule mass. The spraying was repeated three times, followed by maturation at 22℃ under a nitrogen atmosphere for 25 min after each application. The matured granules were then dried at 30℃ under a nitrogen atmosphere for 6 h. Drying was stopped when the crystal water content reached 36.2 wt%.
[0074] V. Quality Control Results The resulting granulated ferrous chloride tetrahydrate secondary particles had a particle size (D50) of 2.1 mm, a free hydrochloric acid content of 0.08 wt%, a total iron content of 27.9 wt%, a water of crystallization content of 36.2 wt%, a bulk density of 1.65 g / cm³, an angle of repose of 28°, a ferric iron content of 0.01 wt%, a dense surface layer thickness of 65 μm, and an open porosity of 10%. All samples were taken from the same dried finished product batch. The particle size distribution, cross-sectional thickness, bulk density, and chemical composition were recorded for each sample batch, sampling mass, testing method, and calculated caliber.
[0075] VI. Applicable Scenarios of this Embodiment This embodiment employs a high number of recycled mother liquor utilizations, a moderately high liquid addition amount, a sufficient number of surface sprayings, and mild drying conditions, making it suitable for preparing granular ferrous chloride tetrahydrate with larger particle size, more intact surface layer, and lower trivalent iron content in industrial production with a high material recycling rate.
[0076] Comparative Example 1: Basically the same as Example 1, except that the particle size D50 of the primary ferrous chloride tetrahydrate crystals was adjusted to 35 μm, and other conditions were kept as follows: dissolved oxygen in deoxygenated tap water 0.5 mg / L, dissolution temperature 40℃, ferrous chloride content in the solution 18 wt%, free hydrochloric acid content 0.05 wt%, nitrogen atmosphere holding for 10 min, cooling rate 5℃ / h, cooling to 15℃ and holding for 0.5 h, free hydrochloric acid content in the surface layer forming liquid 0.20 wt%, liquid addition amount 2 wt%, granulation temperature 18℃, granulation speed 20 rpm, granulation time 5 min, wet particle maturation for 0.5 h, spraying amount 0.5 wt% each time, spraying once, maturation for 10 min after each spraying, and drying at 20℃ under nitrogen atmosphere for 2 h.
[0077] Comparative Example 2: Basically the same as Example 1, except that the particle size D50 of the primary ferrous chloride tetrahydrate crystals was adjusted to 180 μm, and other conditions were kept as follows: dissolved oxygen in deoxygenated tap water 0.5 mg / L, dissolution temperature 40℃, ferrous chloride content in the solution 18 wt%, free hydrochloric acid content 0.05 wt%, nitrogen atmosphere holding for 10 min, cooling rate 5℃ / h, cooling to 15℃ and holding for 0.5 h, free hydrochloric acid content in the surface layer forming liquid 0.20 wt%, liquid addition amount 2 wt%, granulation temperature 18℃, granulation speed 20 rpm, granulation time 5 min, wet particle maturation for 0.5 h, spraying amount 0.5 wt% each time, spraying once, maturation for 10 min after each spraying, and drying at 20℃ under nitrogen atmosphere for 2 h.
[0078] Comparative Example 3: Basically the same as Example 1, except that the amount of liquid added was adjusted to 1.0 wt% of the mass of the primary ferrous chloride tetrahydrate crystals, and other conditions were kept as follows: the particle size D50 of the primary ferrous chloride tetrahydrate crystals was 50 μm, the dissolved oxygen in the deoxygenated tap water was 0.5 mg / L, the dissolution temperature was 40℃, the ferrous chloride content in the solution was 18 wt%, the A2 free hydrochloric acid content was 0.05 wt%, the nitrogen atmosphere was maintained for 10 min, the cooling rate was 5℃ / h, the temperature was lowered to 15℃ and maintained for 0.5 h, the free hydrochloric acid content in the surface layer was 0.20 wt%, the granulation temperature was 18℃, the granulation speed was 20 rpm, the granulation time was 5 min, the wet granules were matured for 0.5 h, the amount sprayed each time was 0.5 wt%, the spraying was done once, the maturation was 10 min after each spraying, and the drying was carried out at 20℃ under a nitrogen atmosphere for 2 h.
[0079] Comparative Example 4: Basically the same as Example 1, except that the amount of liquid added was adjusted to 13.0 wt% of the mass of the primary ferrous chloride tetrahydrate crystals. Other conditions were kept as follows: the particle size D50 of the primary ferrous chloride tetrahydrate crystals was 50 μm, the dissolved oxygen in the deoxygenated tap water was 0.5 mg / L, the dissolution temperature was 40℃, the ferrous chloride content in the solution was 18 wt%, the A2 free hydrochloric acid content was 0.05 wt%, the nitrogen atmosphere was maintained for 10 min, the cooling rate was 5℃ / h, the temperature was lowered to 15℃ and maintained for 0.5 h, the free hydrochloric acid content in the surface layer was 0.20 wt%, the granulation temperature was 18℃, the granulation speed was 20 rpm, the granulation time was 5 min, the wet granules were matured for 0.5 h, the amount sprayed each time was 0.5 wt%, the spraying was done once, the maturation was 10 min after each spraying, and the drying was carried out at 20℃ under a nitrogen atmosphere for 2 h.
[0080] Comparative Example 5: Basically the same as Example 1, except that the granulation speed of the low-shear granulation equipment was adjusted to 90 rpm, and other conditions were kept as follows: the primary crystal size D50 of ferrous chloride tetrahydrate was 50 μm, the dissolved oxygen in the deoxygenated tap water was 0.5 mg / L, the dissolution temperature was 40℃, the ferrous chloride content in the solution was 18 wt%, the free hydrochloric acid content of A2 was 0.05 wt%, the nitrogen atmosphere was maintained for 10 min, the cooling rate was 5℃ / h, the temperature was lowered to 15℃ and maintained for 0.5 h, the free hydrochloric acid content of the surface layer was 0.20 wt%, the liquid addition amount was 2 wt%, the granulation temperature was 18℃, the granulation time was 5 min, the wet granules were matured for 0.5 h, the spraying amount was 0.5 wt% each time, the spraying was done once, the maturation was 10 min after each spraying, and the drying was carried out at 20℃ under a nitrogen atmosphere for 2 h.
[0081] Comparative Example 6: Basically the same as Example 1, except that dissolution, heat preservation, granulation, ripening and drying were all carried out in an air atmosphere, and other conditions were maintained as follows: primary crystal particle size D50 of ferrous chloride tetrahydrate was 50 μm, dissolved oxygen in tap water was 0.5 mg / L, dissolution temperature was 40℃, ferrous chloride content in the solution was 18 wt%, free hydrochloric acid content of A2 was 0.05 wt%, heat preservation for 10 min, cooling rate was 5℃ / h, cooling to 15℃ and heat preservation for 0.5 h, free hydrochloric acid content in the surface layer formation liquid was 0.20 wt%, liquid addition amount was 2 wt%, granulation temperature was 18℃, granulation speed was 20 rpm, granulation time was 5 min, wet particle ripening was 0.5 h, spraying amount was 0.5 wt% each time, spraying was done once, ripening was done for 10 min after each spraying, and drying was done at 20℃ for 2 h.
[0082] Comparative Example 7: Basically the same as Example 1, except that the drying temperature was adjusted to 45℃, while other conditions were kept the same: the primary crystal size D50 of ferrous chloride tetrahydrate was 50μm, the dissolved oxygen in the deoxygenated tap water was 0.5mg / L, the dissolution temperature was 40℃, the ferrous chloride content in the solution was 18wt%, the free hydrochloric acid content of A2 was 0.05wt%, the nitrogen atmosphere was maintained for 10min, the cooling rate was 5℃ / h, the temperature was lowered to 15℃ and maintained for 0.5h, the free hydrochloric acid content in the surface layer was 0.20wt%, the liquid addition amount was 2wt%, the granulation temperature was 18℃, the granulation speed was 20rpm, the granulation time was 5min, the wet granules were matured for 0.5h, the spraying amount was 0.5wt% each time, the spraying was done once, the maturation was 10min after each spraying, and the drying was carried out for 2h under a nitrogen atmosphere.
[0083] Comparative Example 8: Basically the same as Example 1, except that the cooling rate was 30℃ / h, and other conditions were kept as follows: the primary crystal size D50 of ferrous chloride tetrahydrate was 50μm, the dissolved oxygen in the deoxygenated tap water was 0.5mg / L, the dissolution temperature was 40℃, the ferrous chloride content in the solution was 18wt%, the free hydrochloric acid content of A2 was 0.05wt%, the nitrogen atmosphere was maintained for 10min, the temperature was lowered to 15℃ and maintained for 0.5h, the free hydrochloric acid content in the surface layer was 0.20wt%, the liquid addition amount was 2wt%, the granulation temperature was 18℃, the granulation speed was 20rpm, the granulation time was 5min, the wet granules were matured for 0.5h, the spraying amount was 0.5wt% each time, the spraying was done once, the maturation was 10min after each spraying, and the drying was carried out at 20℃ under a nitrogen atmosphere for 2h.
[0084] Comparative Example 9: Essentially the same as Example 1, except that the low-shear granulation and wet particle ripening steps were omitted. Ferrous chloride tetrahydrate primary crystals were spread into a loose layer, then directly sprayed with a surface-forming liquid and dried. Other conditions were maintained as follows: Ferrous chloride tetrahydrate primary crystal particle size D50 of 50 μm, dissolved oxygen in deoxygenated tap water of 0.5 mg / L, dissolution temperature of 40°C, ferrous chloride content in the solution of 18 wt%, free hydrochloric acid content of A2 of 0.05 wt%, nitrogen atmosphere holding for 10 min, cooling rate of 5°C / h, cooling to 15°C and holding for 0.5 h, free hydrochloric acid content in the surface-forming liquid of 0.20 wt%, spraying amount of 0.5 wt% per application, one application, ripening for 10 min after each application, and drying at 20°C under a nitrogen atmosphere for 2 h. This comparative example was used to investigate the synergistic relationship between recrystallization bridging and a dense surface layer.
[0085] Comparative Example 10: Essentially the same as Example 1, except that the surface-forming liquid spraying and post-spraying curing steps were omitted. Instead, granules were formed solely through mixing primary ferrous chloride tetrahydrate crystals with the surface-forming liquid, low-shear granulation, and wet particle curing. Other conditions were maintained as follows: primary ferrous chloride tetrahydrate crystal particle size D50 of 50 μm, dissolved oxygen in deoxygenated tap water of 0.5 mg / L, dissolution temperature of 40°C, ferrous chloride content in the solution of 18 wt%, free hydrochloric acid content of A2 of 0.05 wt%, nitrogen atmosphere holding for 10 min, cooling rate of 5°C / h, cooling to 15°C and holding for 0.5 h, free hydrochloric acid content in the surface-forming liquid of 0.20 wt%, liquid addition amount of 2 wt%, granulation temperature of 18°C, granulation speed of 20 rpm, granulation time of 5 min, wet particle curing for 0.5 h, and drying at 20°C under a nitrogen atmosphere for 2 h. This comparative example was used to investigate the synergistic relationship between recrystallization bridging and a dense surface layer.
[0086] Comparative Example 11: Essentially the same as Example 1, except that the surface-forming liquid was first sprayed onto the surface of the primary ferrous chloride tetrahydrate crystals and allowed to stand for 10 minutes, followed by low-shear granulation. No further surface spraying was performed after granulation. Other conditions were maintained as follows: primary ferrous chloride tetrahydrate crystal particle size D50 of 50 μm, dissolved oxygen in deoxygenated tap water of 0.5 mg / L, dissolution temperature of 40°C, ferrous chloride content in the solution of 18 wt%, free hydrochloric acid content of A2 of 0.05 wt%, nitrogen atmosphere for 10 minutes, cooling rate of 5°C / h, cooling to 15°C and holding for 0.5 hours, free hydrochloric acid content in the surface-forming liquid of 0.20 wt%, total liquid addition of 2 wt%, granulation temperature of 18°C, granulation speed of 20 rpm, granulation time of 5 minutes, wet particle ripening for 0.5 hours, and drying at 20°C under nitrogen atmosphere for 2 hours. This comparative example was used to investigate the synergistic relationship between the low-shear granulation ripening sequence and the surface recrystallization structure.
[0087] Characterization tests: Particle size distribution experiments are used to evaluate whether the D50 of primary ferrous chloride tetrahydrate crystals, wet particles, and dry secondary particles is consistent with the structural design. The principle is based on the particle size distribution data generated by the scattering of incident light by the particle population or by statistical analysis of image size. Laser diffraction particle size analysis is preferred for primary crystals. For secondary and wet particles, a combination of laser diffraction range and microscopic image statistical analysis can be used. The particle size distribution method can refer to ISO 13320:2020, and the sample state, dispersion medium, instrument model, sample pretreatment method, and D50 calculation aperture should be recorded.
[0088] Chemical composition experiments were conducted to evaluate the free hydrochloric acid content, total iron content, ferric iron content, and water of crystallization content of the finished product. Dry granules from the same batch were ground to a representative sample size and then subjected to acid-base titration, iron content titration or spectrophotometry, selective colorimetric determination of ferric iron, and thermogravimetric analysis (TGA) to determine the water of crystallization. The sample mass, titration volume, correction factor, and calculation formula were recorded. Free hydrochloric acid content was expressed as HCl, total iron content as Fe, and the water of crystallization content was calculated based on the weight loss ratio within the corresponding moisture release range in the TGA data. The atmosphere, temperature range, and heating program for the TGA test were also recorded.
[0089] Flowability and bulk density tests are used to evaluate the adaptability of granulation for feeding and packaging. Dry granules are equilibrated at 25°C and 50% relative humidity for 2 hours. The angle of repose is measured using the fixed funnel natural stacking method. Bulk density is calculated by slowly filling the granules with a calibrated graduated cylinder or constant volume cup, leveling the granules, and weighing them. At least three parallel samples are required for the same batch, and the container volume, filling method, and whether compaction treatment is performed are recorded.
[0090] The dense surface thickness and open porosity experiments were used to evaluate whether surface recrystallization and internal channels were balanced. Dry particles were cold-mounted and their cross-sections were polished. The cross-sections were observed using a conventional optical microscope or a standard scanning electron microscope, and the surface thickness of at least 30 particles was recorded. The open porosity was calculated using cross-sectional image binarization, and the threshold and statistical area were recorded.
[0091] Oxidative stability tests were used to evaluate the effects of low-oxygen processes, free hydrochloric acid content, and dense surface layer on the retention of ferrous iron. 10g of the dried finished product was placed in a sealed, humidity-controlled container at 25℃ and 50% relative humidity for 7 days. Samples were taken to measure the change in ferric iron content, and the increment was calculated compared to the initial ferric iron content. Each sample was tested in triplicate.
[0092] The structural integrity test was used to evaluate the contribution of recrystallization bridging and dense surface layer to the particle's resistance to breakage. 50g of dried particles were placed in a drum or standard sieve assembly and treated at 25°C with a fixed rotation speed for 10 minutes. The broken fine powder was collected by sieving, and the wear rate was calculated. Simultaneously, the changes in D50 of the secondary particles before and after treatment were recorded.
[0093] The solubility availability test was used to evaluate the effect of dense surface and open pores on the solubility response during use. 5.0 g of particulate sample was added to 100 mL of deoxygenated water and stirred at 200 rpm at 25 °C. The time it took for the solution to become clear or for no visible particles to remain was recorded, and the recovery rate of ferrous iron in the solution was determined. Each sample was tested in triplicate.
[0094] Figures 1 to 5 This is used to illustrate the influence of the main process parameters in this scheme on the flowability and oxidative stability of granulated ferrous chloride tetrahydrate. Figure 1This diagram illustrates the effect of the primary crystal size D50 of granulated ferrous chloride tetrahydrate on the angle of repose and the 7-day increase in ferric iron. Using the intermediate parameter combination of Example 3 as a baseline, the liquid addition amount was kept constant at 6.0 wt%, the free hydrochloric acid content in the surface layer forming liquid at 0.50 wt%, the spraying amount per application at 2.5 wt%, and the drying temperature at 28°C. Only the primary crystal size D50 was changed to 40-180 μm. The results show that when the primary crystal size is too small, the crystal surface area increases, the tendency for adsorption and aggregation between particles is enhanced, and the angle of repose easily increases. When the primary crystal size is too large, the effective contact points between crystals decrease, recrystallization bridging is insufficient, the stability of the particle structure decreases, and the increase in ferric iron increases. When the primary crystal size D50 is controlled at approximately 75-125 μm, both the angle of repose and the 7-day increase in ferric iron are at a low level, indicating that a suitable primary crystal size is beneficial for constructing stable secondary particles and provides a uniform skeletal foundation for subsequent surface densification.
[0095] Figure 2 This diagram illustrates the effect of the amount of liquid added to granulated ferrous chloride tetrahydrate on the angle of repose and the 7-day increase in ferric iron. Based on a primary crystal particle size (D50) of 100 μm, a surface-forming liquid free hydrochloric acid content of 0.50 wt%, a spraying rate of 2.5 wt%, and a drying temperature of 28 °C, only the amount of liquid added was varied from 1.0 to 12.0 wt%. The results show that when the amount of liquid added is too low, the crystal surface is insufficiently wetted, intergranular recrystallization bridging is inadequate, and stable secondary particles are difficult to form, resulting in a higher angle of repose. When the amount of liquid added is too high, the residual liquid phase on the particle surface increases, increasing the chance of water-oxygen contact and leading to an increase in the increase in ferric iron. When the amount of liquid added is controlled between 4.0 and 8.0 wt%, a good balance can be achieved between intergranular bridging, particle formation, and oxidation inhibition, indicating that an appropriate amount of liquid participating in the recrystallization process is a key condition for balancing fluidity and stability.
[0096] Figure 3 This diagram illustrates the effect of free hydrochloric acid content in the granulated ferrous chloride tetrahydrate surface layer forming solution on the angle of repose and the 7-day increase in ferric iron. Under the conditions of a primary crystal particle size D50 of 100 μm, a liquid addition of 6.0 wt%, a spraying rate of 2.5 wt%, and a drying temperature of 28 °C, the only variation was in the free hydrochloric acid content in the surface layer forming solution, ranging from 0.10 to 1.00 wt%. The results show that when the free hydrochloric acid content is too low, the surface recrystallization and densification are insufficient, making it difficult to effectively reduce the intrusion of water and oxygen into the particle interior; when the free hydrochloric acid content is too high, the system becomes too acidic, increasing the risk of local residual liquid and subsequent oxidation. When the free hydrochloric acid content is approximately 0.35-0.65 wt%, the particle angle of repose is lower, and the 7-day increase in ferric iron is also smaller, indicating that moderate acidity can promote surface continuity and densification while avoiding adverse effects caused by excessive liquid phase or excessive acidity.
[0097] Figure 4 This diagram illustrates the effect of the amount of granulated ferrous chloride tetrahydrate sprayed per application on the angle of repose and the 7-day increase in ferric iron. Based on a primary crystal particle size (D50) of 100 μm, a liquid addition of 6.0 wt%, a free hydrochloric acid content in the surface-forming liquid of 0.50 wt%, and a drying temperature of 28℃, only the amount of each application was varied from 0.2 to 6.0 wt%. The results show that when the amount of a single application is too low, the surface-forming liquid cannot continuously cover the particle surface, resulting in insufficient surface densification; when the amount of a single application is too high, the particles are locally over-wetted, easily leading to liquid phase enrichment and increased oxidation. When the amount of each application is controlled between 1.5 and 3.5 wt%, a relatively uniform recrystallized layer forms on the particle surface, and both the angle of repose and the increase in ferric iron remain at a low level. This indicates that multiple, appropriate applications are beneficial for forming an effective barrier surface without significantly increasing the risk of oxidation.
[0098] Figure 5 This diagram illustrates the effect of drying temperature on the angle of repose and the 7-day increase in ferric chloride (Fe3+) in granulated ferrous chloride (Fe3+) particles according to this scheme. Based on a primary crystal particle size (D50) of 100 μm, a liquid addition of 6.0 wt%, a free hydrochloric acid content in the surface-forming liquid of 0.50 wt%, and a spraying rate of 2.5 wt%, only the drying temperature was varied between 15-40℃. The results show that when the drying temperature is too low, the removal of residual liquid phase on the particle surface and in the pores is insufficient, affecting particle flowability; when the drying temperature is too high, the oxidation reaction accelerates, and the increase in ferric iron increases significantly. When the drying temperature is controlled at approximately 24-32℃, the particles exhibit a lower angle of repose and a lower oxidation increase, indicating that gentle drying can achieve a better balance between removing residual liquid phase and inhibiting oxidation.
[0099] Figures 6 to 8 This paper further explains the particle size distribution, granulation degree, and wear resistance of the secondary particles obtained by this method. Figure 6 The diagram shows the differential particle size distribution of the secondary particles in Example 1 and the comparative sample, comparing the particle size distribution of the secondary particles in Example 1, Comparative Example 1, and Comparative Example 9. The results show that the differential particle size distribution peak of Example 1 is concentrated around 0.8 mm, and the peak shape is relatively narrow, indicating that the obtained secondary particles have a concentrated particle size and good particle formation consistency. The particle size of Comparative Example 1 is generally smaller and the distribution is wider, while the proportion of fine powder in Comparative Example 9 is higher, indicating that without a proper bridging or maturation process, the particles are difficult to grow stably. Figure 7 The cumulative particle size distribution of secondary particles in Example 1 and the comparative sample is shown. The cumulative curve of Example 1 shifts to the right overall, with a D50 of approximately 0.8 mm, indicating that its secondary particles are larger and more stably distributed. In contrast, the cumulative curves of Comparative Examples 1 and 9 rise earlier, indicating a higher content of fine particles. These results demonstrate that the proposed method, through primary crystal recrystallization bridging, can effectively reduce the proportion of fine powder, increase the degree of granulation, and thus improve the flowability during processing and transportation.
[0100] Figure 8 This diagram shows the D50 values of the secondary particles in Example 1 and the comparative sample before and after wear, used to compare the particle size retention of Example 1, Comparative Example 1, and Comparative Example 9 before and after the wear test. The results show that the D50 of Example 1 before wear was approximately 0.80 mm, and remained at approximately 0.78 mm after wear, indicating a relatively small decrease in particle size. In contrast, the D50 of Comparative Example 1 and Comparative Example 9 decreased more significantly after wear, indicating insufficient internal bonding strength or poor surface structure stability. These results demonstrate that the secondary particles formed by this method not only have a concentrated particle size but also possess high wear resistance and anti-pulverization ability, which is beneficial for reducing pulverization during packaging, transportation, and feeding processes.
[0101] Figures 9 to 11 The reasons for the structural integrity of this scheme are explained from three aspects: internal particle connectivity, crack defects, and surface construction. Figure 9 The diagram shows the intercrystalline connectivity density of Example 1 and Comparative Example 9, with the number of bridging or connections between crystals counted through cross-sectional images. The results show that the intercrystalline connectivity density of Example 1 is mainly distributed at approximately 18-23 connections / mm², while that of Comparative Example 9 is mainly distributed at approximately 4-7 connections / mm². This indicates that in Example 1, the primary crystals formed a more complete connectivity structure through recrystallization. The increased intercrystalline connectivity density allows the secondary particles to withstand external friction and impact, which is a key reason for its superior wear resistance compared to the comparative sample.
[0102] Figure 10 The figures show the cross-sectional crack ratios of Example 1 and Comparative Example 9, respectively. Analysis of the cross-sectional images revealed the proportion of internal cracks in different particles. The results show that the crack ratio in Example 1 is approximately 2%-4%, significantly lower than the approximately 15%-23% in Comparative Example 9. This indicates that the proposed method, during low-shear granulation and wet particle ripening, can mitigate internal stress concentration within the particles, leading to a more continuous interconnected network between crystals, thereby reducing the proportion of internal cracks and defects. This reduction in crack ratio not only improves particle strength but also reduces the channels for water and oxygen to diffuse inwards along the cracks.
[0103] Figure 11The diagram shows the thickness distribution of the dense surface layer in Examples 1, 10, and 11 of this scheme. The surface layer formation of different samples was statistically compared using multi-particle cross-sections. The results show that the dense surface layer thickness of Example 1 is mainly concentrated at approximately 20-24 μm, with a moderate thickness and relatively stable distribution. The surface layer of Comparative Example 10 is thinner and lacks continuity, making it difficult to form an effective barrier. The surface layer thickness of Comparative Example 11 fluctuates significantly, easily leading to localized excessive thickness or localized deficiencies. This demonstrates that the surface layer formed by recrystallization of a saturated ferrous chloride hydrochloric acid solution in this scheme can construct a dense protective structure of suitable thickness on the outside of the particles, thereby mitigating the adverse effects of water-oxygen contact on oxidation stability during granulation.
[0104] Figures 12 to 15 To further verify the overall effectiveness of this scheme in terms of oxidative stability, solubility, hydration state, and thermal stability. Figure 12 This is a combined graph showing the increase in ferric iron and the dissolution completion time of Example 1 and the comparative sample, used to compare the balance between oxidative stability and solubility of different samples. The results show that the ferric iron increase in Example 1 over 7 days is approximately 0.013 wt%, and the dissolution completion time is approximately 6.0 min, indicating that it maintains a relatively fast dissolution rate while keeping the oxidation increase low. Comparative Examples 6, 10, and 11 show increased oxidation increase, prolonged dissolution time, or decreased overall balance, respectively. These results indicate that the dense surface layer formed by this method does not excessively hinder the dissolution process, and the open pores and moderate intergranular channels retained within the particles can mitigate the adverse effects of the dense structure on solubility.
[0105] Figure 13 This is a combined graph showing the crystal water content and ferric iron content of Example 1 and the comparative sample, used to compare the hydration state and oxidation level of different samples. The results show that the crystal water content of Example 1 is approximately 35.5 wt%, close to the hydration state characteristics of ferrous chloride tetrahydrate, while the ferric iron content remains at a low level. Comparative Examples 6 and 7 have higher ferric iron contents, indicating that they are more prone to oxidation during processing or post-treatment. These results demonstrate that this method can maintain the target hydration structure of ferrous chloride tetrahydrate during granulation and reduce the risk of ferrous iron to ferric iron conversion through acidity adjustment and surface barrier.
[0106] Figure 14 The thermogravimetric (TG) curves of Example 1 and the comparative sample are shown to compare the mass change behavior of Example 1, Comparative Example 6, and Comparative Example 7 during the heating process. The results show that all samples exhibit a continuous weight loss process related to the release of water of crystallization. Among them, the weight loss process of Example 1 is more stable, and the residual mass change matches the hydration state of ferrous chloride tetrahydrate. Figure 15The thermogravimetric (DTG) curves of Example 1 and the comparative sample are shown to further compare the changes in the weight loss rate peaks of different samples. The DTG peak shape of Example 1 is more concentrated and the peak position distribution is more stable, while the weight loss rate peaks of Comparative Examples 6 and 7 show a certain shift or broadening, indicating that their water of crystallization release process is more non-uniform. The TG and DTG results together show that the particles obtained by this method have a more stable hydration structure and a more uniform composition, further proving that the processing did not significantly damage the basic phase characteristics of ferrous chloride tetrahydrate.
[0107] Figure 16 The image shows a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 9, used to verify the rationality of Example 1 in terms of secondary particle formation, primary crystal bridging and dense surface construction from the perspective of microscopic morphology. Figure 16 Image a is a low-magnification SEM image of the final product of Example 1, showing the overall morphology of granulated ferrous chloride tetrahydrate with a D50 of approximately 0.8 mm, indicating that the primary crystals can form complete secondary particles after low-shear granulation and ripening. Figure 16 b is a low-magnification SEM image of the final product of Comparative Example 9, showing that it is mainly composed of loosely packed or locally agglomerated primary crystals of ferrous chloride tetrahydrate with a D50 of about 50 μm. This indicates that after canceling low-shear granulation and wet particle ripening, the system is difficult to form stable secondary particles.
[0108] Figure 16 c is a magnified SEM image of the final product of Example 1, showing the accumulation, contact, and continuity of the primary crystals on the surface of the secondary particles, indicating that the surface-forming liquid participated in the inter-crystal connection and particle surface integration process. Figure 16 Image d is a high-magnification SEM image of the final product of Comparative Example 9, showing insufficient bonding between primary crystals, uneven surface coverage after spraying, and exposed crystal areas, indicating that direct spraying and drying is unlikely to obtain a uniform particle surface. Figure 16 e is a high-magnification SEM or cross-sectional SEM image of the final product of Example 1, showing a dense surface layer of about 20 μm, intergranular recrystallization bridging structure, and the edge of the open pores, indicating that this scheme can retain about 20% of the open porosity while constructing a dense outer layer structure. Figure 16 f is a high-magnification SEM image of the final product of Comparative Example 9, showing discontinuous crystallization layers, localized insufficient coverage, or dispersed crystal surfaces, indicating that the surface-forming liquid struggles to form a continuous and dense surface layer in the absence of a secondary particle framework. The SEM results corroborate the statistical results of particle size distribution, wear, cracks, and surface thickness, supporting the trend of improved particle formation quality and surface structure in the example samples.
[0109] Figure 17The TEM structure comparison diagrams of the final product of Example 1 and the final product of Comparative Example 9 are used to further illustrate the differences in local crystal structure, surface region and intergranular connection structure of the final products. Figure 17 Image a is a bright-field TEM image of the final product of Example 1. The observed objects are crystal fragments, dense surface flakes, or local areas of intercrystalline bridging in the final particles. It shows local crystal edges and interface regions in the granular structure of FeCl2·4H2O, indicating that the final secondary particles are composed of local crystal connecting units. Figure 17 b is a bright-field TEM image of the final product of Comparative Example 9. The observed object is primary crystal fragments or local crystallization fragments formed after direct spraying. Its structure is mainly characterized by dispersed crystals or discontinuous crystallization regions, lacking the more continuous bridging features of Example 1.
[0110] Figure 17 c is an HRTEM image of the final product of Example 1, showing the lattice fringes and locally ordered structure of the FeCl2·4H2O crystal region. This result can be used as a reference for local crystallinity. The hydration state of the final product is judged by combining the crystal water content, thermal analysis results and crystal structure characterization results. Figure 17 Image d is the HRTEM image of the final product of Comparative Example 9, showing that lattice structure or local defect state can also be observed in the primary crystal. This indicates that Example 1 and Comparative Example 9 are not completely different at the level of a single crystal phase. The main difference between the two lies in the particle-level bridging structure and the degree of surface continuity. Figure 17 e represents the SAED result of the final product of Example 1, showing that the FeCl2·4H2O crystal region is crystalline, which helps to illustrate that the local phase of the final particles is compatible with the target material; Figure 17 f represents the SAED result of the final product of Comparative Example 9, used to compare the crystallinity of its primary crystal region, further illustrating that the shortcomings of Comparative Example 9 mainly stem from incomplete granular structure and insufficient surface continuity, rather than simple compositional differences.
[0111] In conclusion, Figures 1 to 5 From the perspective of process parameters, this is used to illustrate the synergistic effects of primary crystal particle size, liquid addition amount, free hydrochloric acid content, single spraying amount, and drying temperature on flowability and oxidative stability. Figures 6 to 11 The formation and stability of secondary particle structures are explained from the perspectives of particle size distribution, wear resistance, intergranular bonding, crack ratio, and surface thickness. Figures 12 to 15 The balance between stability and solubility of particle structure is explained from the perspectives of oxidation increment, dissolution time, hydration state and thermal analysis. Figure 16 and Figure 17The morphology and crystal structure of the above results were then verified at the microstructural level using SEM and TEM. The results of the above implementation collectively demonstrate that this method, by constructing secondary particles through recrystallization bridging of primary crystals and forming a dense surface layer through recrystallization with a saturated ferrous chloride hydrochloric acid solution, effectively solves the problems of balancing the processing fluidity and oxidative stability of ferrous chloride tetrahydrate, and the balance between structural integrity and solubility.
[0112] Table 1 Performance of Examples and Comparative Examples
[0113] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 show a relatively balanced trend in terms of angle of repose, 7-day ferric iron increment, wear rate, dissolution completion time, and bulk density. In the conventional comparative examples, when the primary crystal particle size, liquid addition amount, granulation speed, atmosphere, drying temperature, and cooling rate deviate, the fluidity, oxidation stability, or structural integrity decrease to varying degrees. In the synergistic comparative examples, when the low-shear granulation ripening process, the surface spray ripening process, or the order of the two processes are cancelled, the wear rate and ferric iron increment increase, indicating that the combination of recrystallization bridging, dense surface layer, and low-oxygen process helps to balance the naturally contradictory performance characteristics.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A granulated ferrous chloride tetrahydrate, characterized in that, The granulated ferrous chloride tetrahydrate is a secondary particle with an intergranular recrystallization connection structure formed by multiple primary ferrous chloride tetrahydrate crystals, and the outer layer of the secondary particle has a dense surface layer; wherein, the particle size D50 of the secondary particle is 0.8-2.5 mm, the particle size D50 of the primary ferrous chloride tetrahydrate crystal is 50-150 μm, the free hydrochloric acid content (HCl) is 0.02-0.30 wt%, the total iron content (Fe) is 27.3-28.1 wt%, the water of crystallization content is 35.5-36.2 wt%, the bulk density is 1.2-1.8 g / cm³, the trivalent iron content is ≤0.05 wt%, the thickness of the dense surface layer is 20-80 μm, and the particle porosity of the secondary particle is 8-20%.
2. The granulated ferrous chloride tetrahydrate according to claim 1, characterized in that, The primary ferrous chloride tetrahydrate crystals are prepared by the following steps: A1. Add ferrous chloride tetrahydrate to tap water and dissolve it at 40-65℃; A2. Add hydrochloric acid to the solution obtained in A1 so that the content of ferrous chloride (calculated as anhydrous ferrous chloride) in the solution is 18-22 wt% and the content of free hydrochloric acid (calculated as HCl) is 0.05-0.30 wt%, and keep it at a temperature of 10-60 min under a nitrogen atmosphere. A3. Cool the solution obtained in A2 to 15-25℃ and keep it at that temperature for 0.5-2.0h, then separate the solid and liquid phases to obtain primary ferrous chloride tetrahydrate crystals with a particle size D50 of 50-150μm.
3. The granulated ferrous chloride tetrahydrate according to claim 2, characterized in that, The dense surface layer is formed through the following steps: B1. Ferrous chloride tetrahydrate is added to the mother liquor containing hydrochloric acid obtained from the solid-liquid separation in A3, and a saturated ferrous chloride-hydrochloric acid solution is prepared at 20-30℃, wherein the free hydrochloric acid content is 0.20-0.80 wt% (calculated as HCl). B2. Filter to remove undissolved solids to obtain the surface layer liquid; B3. The surface layer forming liquid obtained in B2 is sprayed onto the surface of wet particles formed by low-shear granulation and ripening of the primary crystals of ferrous chloride tetrahydrate. The amount sprayed each time is 0.5-5.0 wt% of the mass of the wet particles. After each spraying, the particles are ripened for 10-30 minutes. This process is repeated 1-3 times to form the dense surface layer.
4. The granulated ferrous chloride tetrahydrate according to claim 3, characterized in that, The secondary particles are formed through the following steps: C1. Mix the primary ferrous chloride tetrahydrate crystals with the surface-forming liquid, wherein the amount of liquid added is 2-10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals; C2. The mixture obtained in C1 is granulated in a low-shear granulation device at 18-30℃ and 20-60rpm for 5-20min to obtain wet granules; C3. The wet particles obtained from C2 are aged for 0.5-2.0 hours to form recrystallization bridges between adjacent primary crystals.
5. The granulated ferrous chloride tetrahydrate according to claim 4, characterized in that, The wet particles obtained from C3 were dried at 20-35°C under a nitrogen atmosphere for 2-8 hours. The drying was stopped when the water of crystallization content reached 35.5-36.2 wt%, and the granulated ferrous chloride tetrahydrate was obtained.
6. The granulated ferrous chloride tetrahydrate according to claim 5, characterized in that, The granulated ferrous chloride tetrahydrate has an angle of repose of 25-40°.
7. A method for preparing granulated ferrous chloride tetrahydrate as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Add ferrous chloride tetrahydrate to tap water and dissolve it at 40-65℃. Add hydrochloric acid to make the ferrous chloride content (calculated as anhydrous ferrous chloride) in the resulting solution 18-22 wt% and the free hydrochloric acid content (calculated as HCl) 0.05-0.30 wt%. After keeping the solution at a nitrogen atmosphere for 10-60 min, cool the resulting solution to 15-25℃ and keep it at that temperature for 0.5-2.0 h. Separate the solid and liquid to obtain primary ferrous chloride tetrahydrate crystals with a particle size D50 of 50-150 μm. S2. Add ferrous chloride tetrahydrate to the mother liquor containing hydrochloric acid obtained from the solid-liquid separation in step S1, and prepare a saturated ferrous chloride-hydrochloric acid solution at 20-30℃, wherein the free hydrochloric acid content is 0.20-0.80 wt% (calculated as HCl); filter to remove undissolved solids to obtain the surface-forming liquid. S3. Mix the primary ferrous chloride tetrahydrate crystals with the surface forming liquid, wherein the amount of liquid added is 2-10 wt% of the mass of the primary ferrous chloride tetrahydrate crystals; granulate the resulting mixture in a low-shear granulation device at 18-30℃ and 20-60 rpm for 5-20 min, and then mature it for 0.5-2.0 h to obtain wet granules; S4. Spray the surface forming liquid onto the surface of the wet particles 1-3 times, and allow it to mature for 10-30 minutes after each spraying to form a dense surface layer on the outer layer of the wet particles. S5. The particles obtained in S4 are dried at 20-35℃ under a nitrogen atmosphere for 2-8 hours to obtain granulated ferrous chloride tetrahydrate.
8. The preparation method according to claim 7, characterized in that, In step S1, the dissolved oxygen in the solution obtained after adding hydrochloric acid is ≤0.5mg / L, and the cooling rate is 5-20℃ / h.
9. The preparation method according to claim 7, characterized in that, The wet particle size D50 obtained in step S3 is 0.3-1.2 mm; in step S4, the amount sprayed each time is 0.5-5.0 wt% of the mass of the wet particles; the drying endpoint in step S5 is when the water content of crystallization reaches 35.5-36.2 wt%.
10. The preparation method according to claim 7, characterized in that, The mother liquor generated in the preparation method is recycled 1-5 times after being replenished with ferrous chloride tetrahydrate, hydrochloric acid and tap water. The ferrous chloride content in the recycled mother liquor, calculated as anhydrous ferrous chloride, is maintained at 18-22 wt%, and the free hydrochloric acid content, calculated as HCl, is maintained at 0.05-0.80 wt%. The recycled mother liquor used before step S1 is replenished and adjusted so that the free hydrochloric acid content, calculated as HCl, in the solution entering step S1 is maintained at 0.05-0.30 wt%.
Citation Information
Patent Citations
Preparation method of ferrous chloride tetrahydrate
CN111170373A